Aspectos da dinâmica populacional e biologia reprodutiva de Achatina fulica Bowdich, 1822 (Mollusca, Gastropoda) na cidade de Salvador - Bahia - Silva, Eder Carvalho (2013)
The risks of the introduction an invasion species are uncalculated and bigger. Consisting as one of the a hundred species with biggest invade potential, Achatina fulica stand out from others pulmonary land snail, especially, because your highest reproductive potential that accelerates the dispersion process increasing the damage related to health, economics and environment. With the objective of investigating the relationship of the african snail with the environment, was made a study by aspects of population dynamics and reproductive biology in the city of Salvador. The experiment consisted of the monthly manual collection of the snail, morfometric analysis in field and laboratory analysis later (reproductive system). The results showed there to be a yearly cycle for A. fulica with the period of recruitment at the end of the rainy season and in the dry season, growth in height of the shell and the increase of the sexual activity in the rainy season. In spite of the preference for the rainy station, was found snails in the top of sexual activity for whole period of study. Moreover, it was notice that there is a relationship between the peristome thickness and sexual development, with the increase of this structure as the individual reach the sexual maturity but this relationship isn’t precisely and it should be adjust for each area. The eradication becomes impossible because of the invasion levels founded in Salvador, it’s recommended the control of the specie, even it can be in a continue way, it should be intensified in rainy periods.